EPMA maps unveil the actual chemical variations and crystallization sequence of pyroxenes and plagioclase solidified from a basaltic liquid at variable cooling rates - Gennaro E; Radica F; Iezzi G; Vetere F; Nazzari M; Zellmer GF; Scarlato P (Elsevier B V, 2023)
Crystal-chemical variations of pyroxene (px) and plagioclase (plg) have been analysed by X-ray electron microprobe (EPMA) mapping to quantify their actual chemical dispersions. These phases were experimentally crystallised from a basaltic liquid (B100, MORB from Iceland) at cooling rates of 1, 7, 60 and 180 ◦C/h from 1300 ◦C down to 800 ◦C. Experiments were run at ambient conditions applying defined temperature paths mirroring characteristic cooling rates from innermost to outermost portions of metre- to centimetre-thick lavas, dikes and bombs emplaced under submarine to subaerial conditions. As the cooling rate increases from 1 to 180 ◦C/h, the run-products become progressively enriched in pyroxene and depleted in plagioclase, while spinel is invariably low (few area%) and glass is significant only at 180 ◦C/h. An increase of cooling rate generally leads to enrichment of Al2O3 and depletion of MgO in px, while the opposite behaviour is observed for plg; these trends are mirrored by calculated cations (apfu: atom per formula unit) and components. Average variations as a function of cooling rate are similar to those already observed through classical analysis performed by single point EPMA. However, the actual chemical distributions of CaO versus MgO, Al2O3 and FeOtot oxides unveil the presence of a wider range in pyroxene chemistry. In particular, one px (px-1, CaO-rich, diopsidic type) is present at all the applied cooling rates; a very low CaO-px (px-2, pigeonite or orthopyroxene type) is detected at 1 ◦C/h; and, finally, once more population of px (px-3, CaO-poor diopsidic type) appears at 60 and 180 ◦C/h. By contrast, plg analyses yield invariably identical compositions. Textural variations as a function of cooling rate and geo thermometric estimations indicate that px-1 crystallised at high-T (or low ΔT), while plg mainly grew in the residual melt produced by the saturation of px. If only textures were evaluated, this order of segregation would like remain unrecognised since px at low cooling rates is smaller than plg. The abundance of phases, their crystal chemical features, and their order of segregation can be regarded through a theoretical framework of a time temperature-transformation (TTT) diagram. The most significant chemical variations are displayed by MgO and Al2O3 for both px and plg, which faithfully capture the evolution of cooling conditions. The chemical compositions of px-1 is close to the thermodynamic equilibrium only at 1 ◦C/h. As the cooling rates increase, the px chemistry indicates disequilibrium conditions. Finally, this study shows that as ΔT/Δt increases, the most abundant px (px-1) and plg are forced towards compositions that become progressively closer to those of the parental liquid.
Keywords: Basalt; Cooling rate; Kinetics; Plagioclase; Pyroxene